The relationship between Vesalius and the Borgarucci family. Issue 5 (3rd September 2017) - Van Hee, Robrecht
Abstract: Two of the four brothers Borgarucci were medical doctors and in one way or another, be it distantly, connected with the great master Vesalius. Giulio Borgarucci was a physician, who became a Calvinist and emigrated to England where he treated many noblemen and friends of Queen Elisabeth I. He was present at a conversation between the Italian writer and traveler Pietro Bizzari and the Venetian jeweler who witnessed Vesalius' death in Zakynthos. Prospero Borgarucci became professor of anatomy and surgery in Padua, some 20 years after Vesalius. He published several treatises on anatomy, pestilential disease, and materia medica . Prospero Borgarucci became physician to Queen Catherine de Medicis in France, and to Archduke Karl II of Habsburg in Graz. His most important work is the so-called Chirurgia Magna of Vesalius. Text and illustrations of this spurious Vesalian work point to the use of passages of the Epitome, surgical college notes and copied Vesalian images in Borgarucci's Chirurgia Magna .